Stimulating Students’ Argumentation using Drawing – based Modeling on The Concept of Ecosystem - E N Sumarni; A Widodo; R Solihat (Universitas Sebelas Maret, 2017)
Drawing – based modeling as learning approach, it allows students to create models based on drawing which help them to run a simulation. Students can use drawing–based modeling to learn a pair of interacting population known as predato–prey system while they usually conducted practicum using diagram of organisms. This study was to explore students’ argumentation and students’ understanding on the concept of the ecosystem. The study was conducted quasi – experimental using the matching – only post-test – only control group design. The participants consist of 60 grade 10 senior high school students in Subang, West Java. They are placed into two groups, 30 students in the experimental group and 30 students in the control group. Data was collected through argumentation test and selected response test for assessing students’ understanding. Students’ argumentation were analyzed using Toulmin’s argumentation pattern and statistical analysis. The result showed there is no significant difference between the experimental group and the control group for students’ argumentation. Most of the students are predominantly at level 2. But the coherency of arguments of the experimental group is more coherent than the control group. It means that the students in experimental group can make logical claim and supported by the correct and relevant grounds (data, warrant, and backing). The result of students’ understanding showed there is a significant mean score between the experimental group and the control group whether 72.33 for the experimental group and 62.13 for the control group